Environmental constraints on transpiration and stomatal conductance in a Siberian Arctic boreal forest. Issue 3 (11th March 2017) - Kropp, Heather; Loranty, Michael; Alexander, Heather D.; Berner, Logan T.; Natali, Susan M.; Spawn, Seth A.
Abstract: Boreal forest ecosystems are experiencing changes in plant productivity that are likely to continue with ongoing climate change. Transpiration ( T ) and canopy stomatal conductance ( g c ) are a key influence on plant productivity, and a better understanding of drivers and limitations of T and g c is necessary for constraining estimates of boreal ecosystem change. We describe patterns in T and g c of a deciduous conifer, Larix cajanderi, in an arctic boreal forest in northeastern Russia across three growing seasons from 2013 to 2015. We examine the influence of environmental drivers on g c using a phenomenological model. T was highly variable across days and varied between 0.03 and 0.75 L m −2  d −1 . T and g c largely covaried with daily fluctuations in air temperature and vapor pressure deficit. g c was highly suppressed on days when the vapor pressure deficits exceeded 0.75 kPa with an average daily g c of 37.55 mmol m −2  s −1, and the average daily g c was almost double (71.25 mmol m −2  s −1 ) when vapor pressure deficits stayed below 0.75 kPa. Daily variation in g c was significantly related to air temperature, permafrost thaw depth, and past precipitation. The influence of past precipitation and permafrost thaw depth on g c indicates that belowground conditions relating to soil moisture status are a key limitation for T . Such limitations on g c and T suggest that soil water and plant water stress play an important role in plant productivity and water relations in far northeastern Siberia. Key Points: Transpiration and canopy stomatal conductance are highly reduced under moderate vapor pressure deficits Canopy stomatal conductance demonstrated significant responses to precipitation that occurred 4–7 days prior Canopy stomatal conductance is greatly reduced in response to air temperature during the growing season